The impact of gender upon professional perceptions of offending - Howarth-Beal, Jodie A. (2021)
This thesis provides an investigation into professional perceptions of offending based upon the gender of offenders. The thesis adopts a funnel approach by exploring professional attitudes towards people convicted of offences generally and then narrows down to focus on those who have committed sexual offences. The work is composed of a systematic review, an organisational case study, an empirical research study, and a psychometric critique. The systematic review explores the attitudes of professionals towards male and female offenders of any offence type. The results showed some disparity between the gender of offenders, but overall there were limited differences. There was very slight gender bias, with male offenders being viewed more negatively than women, however caution around this finding is discussed due to the small number of studies and heterogeneous nature of them. Additionally, caution is suggested with the results due to sampling bias and methodological variances between the studies. The organisational case study explored the impact of training on the concept of resilience on attitudes towards male and female offenders. This was undertaken with a small cohort of staff members from a youth justice organisation. It is accepted that the wider generalisability of the results is difficult due to the small sample size and lack of statistical power. However, results indicated that training slightly increased positive attitudes towards offenders generally, although statistically only male offenders showed a slightly stronger effect in terms of re-offending. Findings are discussed in terms of clinical applications. The empirical study explored the implicit beliefs held by professionals working within forensic settings and how these impacted on the attitudes of male and females who commit sexual offences. The findings were not as expected, with no differences found in relation to attitudes towards male and female offenders, and with those holding fixed beliefs that sexual offenders are unable to change advocating the use of rehabilitation. Again, findings provide suggestions for further research and for implications of clinical practice. A psychometric critique of the Attitude to Sexual Offenders Scale (ATS; Hogue, 1993) is also included within this thesis. This explored the validity and reliability of the ATS and ATS-21, which demonstrate some areas of limitation but also some very strong areas of merit. The findings of the thesis as a whole are considered within the final chapter, including considerations for further research and applications for clinical practice and the impacts on organisational need.